Greater goods: ethics, energy, and other‐than‐human speech. (12th March 2019) - Howe, Cymene
Abstract: Renewable energy projects are ethically laudable for their cleansing intentions, but they also produce effects upon other‐than‐human beings in their orbit. Taking the case of Mexico's Isthmus of Tehuantepec, which is home to the densest concentration of on‐shore wind parks anywhere in the world, and following Foucault's reading of the speech form 'parrhesia', this essay argues that the bodies of affected nonhuman beings, particularly those whose existence is actively balanced against a 'greater good' for humanity, enact a form of other‐than‐human speech, first in their threatened status and, secondly, through environmental management regimes that seek to synchronize human and nonhuman lives in settings of both local and global ecological failures.